PENGARUH UPAYA PERJANJIAN KERJASAMA PERDAGANGAN AMERIKA SERIKAT TERHADAP PENINGKATAN INTELLECTUAL PROPERTY PROTECTION DAN PEREKONOMIAN NEGARA-NEGARA PARTNER UNITED STATE FREE TRADE AREA - Siswi, Farisah Primarini; Susitianingsih, Hermini; Wahyudi, Fendy Eko (Journal of International Relations, 2016)
This study aims to determine the effect of IPP enforcement efforts undertakenby the United States in order to increase IPP level in United State’s tradingpartner countries. In addition, this study provides an overview of the economicbenefits to countries that enforce the IPP regime effectively. The method usedin this study is quantitative method using software piracy as indicator tomeasure the strength of IPP in every partner countries. The results from thisresearch indicates that the United States trade cooperation through US FTAscheme has significant effect towards the increase of IPP, compared withcoercion through the Special report 301. The increase of IPP is evidenced bythe decrease of software piracy level after US FTA ratification. This study alsofinds significant relationship between the increase of IPP level on the influx offoreign direct investment in the United States’s trading partner countries, as afigure of economic benefit received by those countries for enforcing IPPregime under US FTA scheme.